1999
DOI: 10.1002/(sici)1521-4141(199902)29:02<499::aid-immu499>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Distinct regulation of HLA class II and class I cell surface expression in the THP-1 macrophage cell line after bacterial phagocytosis

Abstract: Expression of HLA and CD1b molecules was investigated in the THP-1 macrophage cell line within 2 weeks following phagocytosis of mycobacteria or Escherichia coli. During the first 2-3 days, cell surface expression of HLA class II and CD1b was drastically down-modulated, whereas HLA class I expression was up-modulated. In the following days both HLA class II and CD1b expression first returned to normal, then increased and finally returned to normal with kinetics similar to that observed for the steadily increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
2

Year Published

2000
2000
2010
2010

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 25 publications
3
21
2
Order By: Relevance
“…Because CIITA plays a central role in the expression of MHC class II genes that are crucial to the protective immune responses mounted by the host, many pathogens have developed ways of interfering with the function or expression of CIITA (30). For example, phagocytosis of gram-negative bacteria (eg, Escherichia coli) and mycobacteria by human macrophages is accompanied by the down-regulation of MHC class II molecules as a consequence of the reduced transcription of CIITA (31). Viruses and bacteria can interfere at various steps of the pathway that mediates the induction of CIITA expression in immune cells by interferon-g (20).…”
Section: Discussionsupporting
confidence: 64%
“…Because CIITA plays a central role in the expression of MHC class II genes that are crucial to the protective immune responses mounted by the host, many pathogens have developed ways of interfering with the function or expression of CIITA (30). For example, phagocytosis of gram-negative bacteria (eg, Escherichia coli) and mycobacteria by human macrophages is accompanied by the down-regulation of MHC class II molecules as a consequence of the reduced transcription of CIITA (31). Viruses and bacteria can interfere at various steps of the pathway that mediates the induction of CIITA expression in immune cells by interferon-g (20).…”
Section: Discussionsupporting
confidence: 64%
“…Indeed we could show that the antigen processing and presenting competence of the THP-1 macrophage cell line was severely hampered by the Tat mutants. This was best appreciated in IFN-+ -treated THP-1 cells, as normal cells did not display detectable antigen presenting capacity (this study and [28]). In fact, the HLA class II down-modulation brought about by the Tat mutants quantitatively correlated with the impairment in APC functions.…”
Section: Discussionmentioning
confidence: 72%
“…The expression of costimulatory molecules, such as CD80 and CD86, also increased following 96 h of bacterial stimulation. Interestingly, the expression of HLA-DR was down-regulated by bacterial treatment, as previously observed with heat-killed Mycobacterium bovis and Escherichia coli (5). Using peripheral blood monocytes we have demonstrated that the phenotypic modifications observed following bacterial stimulation were not restricted to the monocytic THP-1 cell line.…”
Section: Discussionmentioning
confidence: 99%